FAKTOR YANG MEMPENGARUHI MINAT KEWIRAUSAHAAN MENJALANKAN USAHA MINUMAN DI KECAMATAN TAMPAN KOTA PEKANBARU - Roni Putra; Wilson Wilson; Said Suhil Achmad (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
This research is motivated by factors that influence entrepreneurial interest, so researchers want to examine which factors are the most dominant influencing factors that influence entrepreneurial interest in running a beverage business in Tampan District, Pekanbaru City. So that the researcher formulates the problem under study, which is the most dominant factor influencing entrepreneurial interest in running a beverage business in Tampan District, Pekanbaru City?. This type of research is descriptive with a quantitative approach. The population in this study were beverage entrepreneurs in the Tampan District of Pekanbaru City as many as 70 people. The technique used is Simple Random Sampling. Based on the test results, for data from the variable factors that influence entrepreneurial interest in running a beverage business, the number of valid data is 41 and invalid data is 3. All invalid items are discarded meaning they are not used in the study, because all valid items represent indicators and sub-indicators. Based on the results of the analysis, it can be seen that the first indicator is that external factors are higher than internal indicators with an average mean of 0.99 and an SD of 0.77 which is in a high interpretation. Internal factor indicators with a mean value of 3.97 and an SD of 0.76 which are also in a high interpretation. The average number of all indicators means 3.98 and SD 0.76 which are in the high interpretation. This means that entrepreneurs who run a beverage business in the Tampan District of Pekanbaru City are due to external factors, namely the feeling of satisfaction in running a beverage entrepreneur because of the income they get when opening a business.Key Words: Factors Entrepreneurial Interest.